Crypto Dowry Acceptance Among Muslim Millennials: Theory of Planned Behavior with Religiosity Moderation - Ahmad Syafii Rahman; Nugroho , Taufik (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2026)
This study examines the acceptance of digital dowries among Indonesian Muslim millennials using the Theory of Planned Behavior (TPB), with religiosity as a moderating variable and digital literacy as a direct determinant. The growing use of digital assets, such as cryptocurrencies, NFTs, and e-money, in marriage practices reflects financial digitalization and raises ethical and Sharia-related concerns. This study adopts a quantitative explanatory approach, collecting survey data from 200 Muslim millennials in Indonesia and analyzing it using Structural Equation Modeling (SEM) in AMOS. The findings show that attitude (β = 0.256; p < 0.001), subjective norms (β = 0.342; p < 0.001), and perceived behavioral control (β = 0.177; p = 0.010) significantly influence the acceptance of digital dowries. Digital literacy also has a significant direct effect (β = 0.191; p = 0.003). Religiosity partially moderates the relationship between attitude and digital dowry acceptance (β = 0.188; p = 0.004). These results indicate that acceptance of digital dowry is driven by behavioral, social, and technological factors, with religiosity serving as a selective ethical filter. The study offers implications for policymakers and religious authorities in formulating Sharia-responsive guidelines for digital marriage practices.